Firm-to-Firm Relationships and Price Rigidity - Theory and Evidence - Sebastian Heise (Center for Economic Studies and ifo Institute (CESifo), 2016)
Economists have long suspected that firm-to-firm relationships might increase price rigidity due to the use of explicit or implicit fixed-price contracts. Using transaction-level import data from the U.S. Census, I study the responsiveness of prices to exchange rate changes and show that prices are in fact substantially more responsive to these cost shocks in older versus newly formed relationships. Based on additional stylized facts about a relationship's life cycle and interviews I conducted with purchasing managers, I develop a model in which a buyer-seller pair subject to persistent, stochastic shocks to production costs shares profit risk under limited commitment. Once structurally estimated, the model replicates the empirical correlation between relationship age and the responsiveness of prices to shocks. My results suggest that changes to the average length of relationships in the economy - e.g., in a recession, when the share of young relationships declines - can influence price exibility and hence the effectiveness of monetary policy.
Keywords: E30; F10; F20; 330; relationships; price rigidity; pass through